Pemanfaatan Limbah Botol Plastik Menjadi Kreasi Tempat Pensil Untuk Meningkatkan Kreativitas Anak - Enes Oryza Sativa; Indah Nurmahanani; Rayhansyach Genevieve Kurniawan; Adrias Kasman (Universitas Pendidikan Indonesia Kampus Purwakarta, 2023)
One of the most serious problems faced by people in Indonesia is the waste problem. Waste is an object that is often the cause of environmental pollution, especially plastik waste. In Bantar Gebang District, there are various types of waste, such as plastik waste, household waste and organic waste. Seeing this, a plastik waste recycling program was formed by children. In addition to utilizing plastik waste, this program can also increase children's creativity. The method used in this program is Research Development (RD). The target of this program is children aged 6 to 9 years. The result of this program is a pencil case that children can use to store writing utensils to make it more tidy and also reduce plastik waste in the area around the Bantar Gebang neighborhood, Bekasi City.